No Matter How You Slice It, Black Students Are Punished More: The Persistence and Pervasiveness of Discipline Disparities - Sean Darling-Hammond; Eric Ho (SAGE Publishing, 2024)
Years ago, a groundbreaking review of student data from the 2013-2014 school year indicated that Black students were overrepresented among those experiencing punishment in a variety of contexts. In the intervening decade, new data has emerged, schools have implemented policies to reduce racial disparities, researchers have highlighted new methods of measuring disparities, and pundits have reignited debates about the degree and pervasiveness of disparities. Clarity is needed. Are Black students experiencing more exclusion and punishment than their peers? If so, of what kinds and in what contexts? This article responds by reviewing the most recent federal data, measuring Black overrepresentation across six types of punishment, three comparison groups, 16 subpopulations, and seven types of measurement. We generate 1,581 unique estimates of Black overrepresentation and find evidence that, no matter how you slice it, Black students are overrepresented among those punished. We conclude with policy recommendations to reduce widespread and enduring racial disparities.